NITROGEN FERTILIZATION FOR DRY BEANS UNDER NO TILLAGE SYSTEM - PIASKOWSKI, Sérgio Roberto; RONZELLI JÚNIOR, Pedro; DAROS, Edelclaiton; KOEHLER, Henrique Soares (Scientia Agraria, 2001)
Field trials were carried out in the agricultural years of 1996/97 and 1997/98, respectively, at the Universidade Estadual de Ponta Grossa Farm School, and at the Colégio Agrícola de Palmeira Farm. Both places have eight years history of no tillage system. The objective was to study nitrogen fertilization for dry beans under no till system. There were evaluated yield and their components of the dry beans culture at harvest, and morphological modifications and dry matter of the plant at different vegetative stadium, from V29. The experimental design employed was a randomized complete block, with six treatments (0, 20, 40, 60, 80 and 100 kg of N.ha-1) and five replications with the 'FT Nobre' dry beans variety. Even considering the large number of variables determination, only a few showed significant statistical differences. The yield and components confirmed the nitrogen effect instability on no till system for dry beans culture. Anyway, disconsidering the statistical differences, both experiments showed high yield, like more then twice the State of Paraná average and like four times the country one. Both experiments showed that morphological aspects and MS determination of the plant or parts of them, produced results that agree with the yield results. The conclusion is that it is not possible to confirm that the organic matter presence, very common on no till system, conduct to less exigency for nitrogen and confirm that the dry beans culture answers for nitrogen fertilization, either at no till system, are so variable.